Examining the Influence of Religious and Spiritual Beliefs on HPV Vaccine Uptake Among College Women - Best, Alicia L. (Journal of religion and health, 2019)
The human papillomavirus (HPV) vaccine is an effective mechanism to prevent HPV-associated cancers; however, uptake is low among women aged 18-26. Religiosity/spirituality is associated with sexual health decision-making. This study examined the role of religious/spiritual beliefs on HPV vaccination among college women (N = 307) using logistic regression and mediation analyses. Findings indicate that sexual activity is the main factor associated with HPV vaccination; and sexual activity fully mediates the relationship between religious/spiritual beliefs and HPV vaccination. Health promotion efforts should highlight the importance of HPV vaccination regardless of current sexual activity and may benefit from partnerships with religious/spiritual organizations.